DESIGN AND FABRICATION OF A FLOW CELL PLATFORM USING 3D PRINTING METHOD FOR THE INTEGRATION OF MULTI SCREEN PRINTED ELECTRODE-BASED SENSOR FOR THE DETECTION OF SODIUM AND POTASSIUM IONS - Chyntia H.A., Anchelmia
Microfluidics is a field of study and technology that explores the behavior of fluids and manufacturing techniques for fluid manipulation on a small scale. Microfluidics holds the potential for advancements in the miniaturization of experiments, making it highly conducive to continuous development. The use of 3D printing technology represents a significant development in manufacturing techniques to create flexible and cost-effective microfluidic platforms. Meanwhile, the functional development of microfluidics can be achieved through its integration with other fields, such as biosensors. The integrated flow-cell platform aids the biosensing process by providing a closed detection environment, reducing costs and time, and allowing better fluid control access. In this final project, the fabrication of a flow cell was conducted using 3D printing methods. The printed results demonstrated good accuracy with errors in microchannel and sensor slot designs of less than 14%. Leveraging the flexibility of this method, exploration and optimization were conducted for the design of flow cells for integration with single and multi electrochemical sensors for the detection of sodium and potassium ions in the body. Based on the conducted tests, the detection process of sodium and potassium in a single-sensor integrated flow cell proceeded well, with respective Limits of Detection (LOD) of 0.149 mM and 51,461 ?M. Meanwhile, in the measurement of mixed sodium and potassium solutions using a multi-sensor integrated flow cell, differences in the selectivity of sodium and potassium sensors were obtained. The sodium sensor reading only changed by 0.111% in the presence of potassium ions, whereas the potassium sensor reading changed by 29.530% in the presence of sodium ions. Both the single-sensor and multi-sensor integrated flow cells facilitated measurements under dynamic flow conditions successfully, with maximum flow rates for sodium, potassium, and mixed sodium and potassium solutions being below 10 mL/hour, 50 mL/hour, and 25 mL/hour, respectively.